2007
DOI: 10.1074/jbc.m704893200
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Glutathione Content, Calcium Current, and Contractility

Abstract: Atrial fibrillation (AF) is characterized by decreased L-type calcium current (I Ca,L ) in atrial myocytes and decreased atrial contractility. Oxidant stress and redox modulation of calcium channels are implicated in these pathologic changes. We evaluated the relationship between glutathione content (the primary cellular reducing moiety) and I Ca,L in atrial specimens from AF patients undergoing cardiac surgery. Left atrial glutathione content was significantly lower in patients with either paroxysmal or persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 57 publications
4
71
1
Order By: Relevance
“…Under pathophysiological conditions, however, intracellular GSH levels are often depleted, which significantly affects cell function, including ion channel activity (7,43). As a result, strategies to increase intracellular GSH levels have often been shown to restore cell function, and one such strategy is to supplement cells with exogenous GSH as we have done in the present study.…”
Section: Electrophysiological Effects Of Gsh Omentioning
confidence: 76%
“…Under pathophysiological conditions, however, intracellular GSH levels are often depleted, which significantly affects cell function, including ion channel activity (7,43). As a result, strategies to increase intracellular GSH levels have often been shown to restore cell function, and one such strategy is to supplement cells with exogenous GSH as we have done in the present study.…”
Section: Electrophysiological Effects Of Gsh Omentioning
confidence: 76%
“…Furthermore, this disruption in Ca 2ϩ homeostasis is closely linked to ventricular tachycardia, arrhythmias, and sudden cardiac death (45,46). Similarly, increased S-nitrosylation of the ␣ 1c subunit of the L-type calcium channel is observed in patients with atrial fibrillation (47), in this case associated with a decreased calcium influx.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial I CaL is also regulated by NO through complex pathways involving cGMPdependent PKG, cGMP-inhibited phosphodiesterases, and Snitrosylation of the ␣ 1c -subunit (31,40,47,49). It has been suggested that oxidative stress may contribute to the development of the arrhythmic substrate and downregulation of I CaL during atrial remodeling and this may involve changes in the NO-dependent regulation of L-type Ca 2ϩ channels (11,21,43). The previously reported changes in atrial intracellular cGMP production together with the increased effect of phosphodiesterase inhibition on I CaL are consistent with the proposal that changes in NO/cGMP-dependent regulation of Ltype Ca 2ϩ channels may underlie both the reduced basal current and increased sensitivity to noradrenergic agonism in heart failure (4,19).…”
Section: Discussionmentioning
confidence: 99%